Characterization of low affinity Fcγ receptor biotinylation under controlled reaction conditions by mass spectrometry and ligand binding analysis. (19th August 2016) - Geuijen, Karin P.M.; Egging, David F.; Bartels, Stefanie; Schouten, Jan; Schasfoort, Richard B.; Eppink, Michel H.
Abstract: Chemical protein biotinylation and streptavidin or anti‐biotin‐based capture is regularly used for proteins as a more controlled alternative to direct coupling of the protein on a biosensor surface. On biotinylation an interaction site of interest may be blocked by the biotin groups, diminishing apparent activity of the protein. Minimal biotinylation can circumvent the loss of apparent activity, but still a binding site of interest can be blocked when labeling an amino acid involved in the binding. Here, we describe reaction condition optimization studies for minimal labeling. We have chosen low affinity Fcγ receptors as model compounds as these proteins contain many lysines in their active binding site and as such provide an interesting system for a minimal labeling approach. We were able to identify the most critical parameters (protein:biotin ratio and incubation pH) for a minimal labeling approach in which the proteins of choice remain most active toward analyte binding. Localization of biotinylation by mass spectrometric peptide mapping on minimally labeled material was correlated to protein activity in binding assays. We show that only aiming at minimal labeling is not sufficient to maintain an active protein. Careful fine‐tuning of critical parameters is important to reduce biotinylation in a protein binding site.